Chidra - Arik Moran; Nadav Harel (Journal of Anthropological Films, 2023)
In the mountainous interior of the Himalaya, a highland peasant transforms into a redeemer by cutting holes (chidra) in the social fabric to be delivered to the gods through his body as sacrificial victim. Closely observing this unique ritual-spectacle, CHIDRA. examines how men, gods, and mediums handle the dangerous substance of actions (karma) at the frontier of the Hindu cultural sphere.